Proceso de atención de enfermería en gestante de 12 semanas con amenaza de aborto. - Trujillo Bajaña, Gina Alexandra (2021)
Abortion has been considered one of the most common complications of pregnancy and has become one of the most frequent obstetric emergencies in Los Ríos Province Hospitals that provide Gynecology and Obstetrics services, without discarding the care provided in the hospital. first level of care; At present it is recognized as an important health problem that affects our society, this is due to the fact that the real figures are not known because this procedure, when it does not occur spontaneously and is induced, is performed clandestinely. This clinical case study had the purpose of Developing the Nursing Care Process in a pregnant patient of 16 years of age with 12 weeks and a diagnosis of threatened abortion, taking into account her clinical picture, signs, symptoms, and related risk factors. to the termination of pregnancy (environmental, socioeconomic, genetic) and pathological antecedents (present comorbidities), admitted to the Baba Basic Hospital. An investigative study was carried out by reviewing the patient's medical history, observing her behavior in real time and the way she reacted to the abortion. In addition, a care plan was developed and applied through the Nursing Care Process (PAE), in order to help the patient recover in less time and in a better way, obtaining favorable results after the evaluation of the procedure. through the nursing staff.